Potential use of gold-silver core-shell nanoparticles derived from Garcinia mangostana peel for anticancer compound, protocatechuic acid delivery - Lee, Kar Xin; Shameli, Kamyar; Nagao, Yuki; Yew, Yen Pin; Teow, Sin-Yeang; Moeini, Hassan (Frontiers in Molecular Biosciences, 2022)
Colorectal cancer is one of the most killing cancers and this has become a global problem. Current treatment and anticancer drugs cannot specifically target the cancerous cells, thus causing toxicity towards surrounding non-cancer cells. Hence, there is an urgent need to discover a more target-specific therapeutic agent to overcome this problem. Core-shell nanoparticles have emerged as good candidate for anticancer treatment. This study aimed to synthesize core-shell nanoparticles via green method which utilised crude peels extract of Garcinia mangostana as reducing and stabilising agents for drug delivery. Gold-silver core-shell nanoparticles (Au-AgNPs) were synthesized through seed germination process in which gold nanoparticles acted as the seed. A complete coating was observed through transmission electron microscopy (TEM) when the ratio of AuNPs and AgNPs was 1:9. The size of Au-AgNPs was 38.22 ± 8.41 nm and was mostly spherical in shape. Plant-based drug, protocatechuic acid (PCA) was loaded on the Au-AgNPs to investigate their anticancer activity. In HCT116 colon cancer cells, PCA-loaded Au-AgNPs (IC50=10.78 μg/ml) showed higher inhibitory action than the free PCA (IC50= 148.09 μg/ml) and Au-AgNPs alone (IC50= 24.36μg/ml). Up to 80% inhibition of HCT116 cells was observed after the treatment of PCA-loaded Au-AgNPs at 15.63 μg/ml. The PCA-loaded Au-AgNPs also showed a better selectivity towards HCT116 compared to CCD112 colon normal cells when tested at the same concentrations. These findings suggest that Au-AgNPs system can be used as a potent nanocarrier to combat cancerous cells by offering additional anticancer properties to the loaded drug.